2012
DOI: 10.1007/s00705-012-1360-5
|View full text |Cite
|
Sign up to set email alerts
|

A suggested new bacteriophage genus: “Viunalikevirus”

Abstract: We suggest a bacteriophage genus, “Viunalikevirus”, as a new genus within the family Myoviridae . To date, this genus includes seven sequenced members: Salmonella phages ViI, SFP10 and ΦSH19; Escherichia phages CBA120 and PhaxI; Shigella phage phiSboM-AG3; and Dickeya phage LIMEstone1. Their shared myovirus morphology, with comparable head sizes and tail dimensions, and genome organization are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 31 publications
2
88
0
Order By: Relevance
“…Thus, the amino acid sequences of a structural protein (major capsid protein) and a nonstructural protein (DNA polymerase) were chosen to perform phylogenetic analyses. Previously, major capsid proteins and DNA polymerase were often used as phylogenetic markers (26,34,41). As expected from the phage morphology and the genomic comparison analyses, the phylogeny revealed that MAM1 is closely related to ViI-like phages (see Fig.…”
Section: ϫ6mentioning
confidence: 71%
See 4 more Smart Citations
“…Thus, the amino acid sequences of a structural protein (major capsid protein) and a nonstructural protein (DNA polymerase) were chosen to perform phylogenetic analyses. Previously, major capsid proteins and DNA polymerase were often used as phylogenetic markers (26,34,41). As expected from the phage morphology and the genomic comparison analyses, the phylogeny revealed that MAM1 is closely related to ViI-like phages (see Fig.…”
Section: ϫ6mentioning
confidence: 71%
“…Most of the sequenced ViI-like phages encode four tail spike proteins (26), and the presence of these TSPs has been confirmed by mass spectrometry analyses in Vi01 (32) and LIMEstone1 (11). The MAM1 genome also encodes four putative TSPs, three of which (MAM_031, MAM_034, MAM_037) contain a pectate lyase domain (see Table SA2 in the supplemental material).…”
Section: ϫ6mentioning
confidence: 90%
See 3 more Smart Citations